Implementation of Community Land Rights Acquisition for Public Interest and National Development within a Just Legal Framework in Indonesia - Meidizon; Suparto; Ellydar Chaidir; Surizki Febrianto (CV Edujavare Publishing, 2026)
This study analyzes the implementation of land acquisition for public interest and national development within a justice-based legal framework in Indonesia. Using normative legal research with statutory and case approaches, this study finds that although legal regulations formally accommodate principles of justice, implementation gaps remain evident. Key issues include compensation mechanisms, limited public participation, and weak legal protection. The study concludes that a responsive and integrative legal framework is required to balance development interests and community rights while strengthening long-term legitimacy of land governance.